2019
DOI: 10.4314/njt.v38i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimisation of machining parameters in turning AISI 304L using different oil-based cutting fluids

Abstract: Properties of melon seed and beniseed oils which are considered as "environmentally" friendly oils were investigated and the performance evaluation of the formulated beniseed and melon seed oilbased cutting fluids were carried out. American Iron and Steel Institute (AISI) 304L alloy steel was used as workpiece and tungsten carbide as cutting tool, while commercial mineral oil-based cutting fluid was used as a control experiment. The viscosities of the melon seed oil and beniseed oil-based cutting fluids were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
3
8
0
Order By: Relevance
“…It indicates that feed rate is the most significant parameter that influences the cutting temperature in this study. This is in agreement to the work by [23].…”
Section: Analysis Of Variancesupporting
confidence: 94%
See 4 more Smart Citations
“…It indicates that feed rate is the most significant parameter that influences the cutting temperature in this study. This is in agreement to the work by [23].…”
Section: Analysis Of Variancesupporting
confidence: 94%
“…From Table 5, it could be observed that the viscosity of the formulated rubber seed oil based cutting fluid is 4.25 mm 2 /s and is in agreement with the viscosity 4.39 mm 2 /s of castor oil emulsion cutting fluid [26]. The rubber seed oil based cutting fluid with pH value of 8.3 compares favourably with the pH value 8.2 of melon seed oil cutting fluid [23]. The stability test of the cutting fluids as described in section 2.2.3, showed that there was no phase separation of oil and water which indicates that the cutting fluid is stable.…”
Section: Characterization Of the Formulated Cutting Fluidmentioning
confidence: 53%
See 3 more Smart Citations